A robust tracking control scheme for a class of nonlinear systems with fuzzy nominal model - Mei, Fei; Zhihong, Man; Yu, Xinghuo; Nguyen, Thong (Zielona Góra: Uniwersytet Zielonogórski)
A novel robust tracking control scheme is proposed for a class of nonlinear systems. It is shown that a nonlinear system is first approximated by a fuzzy nominal model by aggregating a set of linearized local subsystems and then a conventional linear feedback controller is designed to stabilise the nominal system.
Keywords: sterowanie; sterowanie-teoria; sztuczna inteligencja; matematyka stosowana; informatyka